Silently transformable: the many ways bacteria conceal their built-in capacity of genetic exchange - Attaiech, Laetitia; Charpentier, Xavier (Current genetics, 2017)
Bacteria can undergo genetic transformation by actively integrating genetic information from phylogenetically related or unrelated organisms. The original function of natural transformation remains a subject of debate, but it is well established as a major player in genome evolution. Naturally transformable bacteria use a highly conserved DNA uptake system to internalize DNA and integrate it in their chromosome by homologous recombination. Expression of the DNA uptake system, often referred to as competence, is tightly controlled and induced by signals that are often elusive. Initially thought to be restricted to a few bacterial species, natural transformation increasingly seems widespread in bacteria. Yet, the triggering signals and regulatory mechanisms involved appear diverse and are understood only in a limited set of species. As a result, natural transformation in most bacterial species remains poorly documented and the potential impact of this mechanism on global genetic mobilization is likely underappreciated. Indeed, even when a conserved activator can be identified to artificially induce the expression of the DNA uptake system, the considered species may still remain non-transformable. Recent works indicate that the DNA uptake system is directly subjected to silencing. At least in Legionella pneumophila and possibly in other species, a small non-coding RNA prevents expression of the DNA uptake system. Silencing constitutes one more way bacteria control expression of their engine of genetic exchange. It may also be the underlying reason of the undetectable natural transformation of many bacterial species grown under laboratory conditions even though they possess a DNA uptake system.